Reimagining Islamic Justice: Unveiling Civic Perceptions of The Religious Court in Urban Bogor - Otom Mustomi; Achmad Faqih (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
Justice is a core principle in Islamic law, aimed at ensuring balance and legal certainty. This study explores public perceptions of Islamic justice in Bogor City using library research and empirical methods, including interviews and surveys. It examines how justice is interpreted and what sociocultural factors influence these views. Findings show that justice is rooted in the Qur’an, Hadith, and classical scholarship. However, interpretations vary depending on education, social background, and familiarity with national law. Some view justice through Islamic moral values, while others see it within state legal frameworks. This divergence reveals a cognitive and normative gap in understanding Islamic justice. The study highlights the need for legal literacy, integrated religious education, and inclusive policy. It encourages collaboration among scholars, legal experts, and policymakers to promote a more coherent and accessible understanding of justice that reflects both religious teachings and modern societal needs